Generalized Muscular Hypermetabolism Caused by Mitochondrial Myopathy Shown on 18F-FDG PET/CT. (12th April 2023) - Liang, Menglin; Wu, Meiqi; Jia, Chenhao; Guo, Ruijie; Cui, Ruixue
Abstract: An 18-year-old man presented with progressive exercise intolerance and muscle weakness for 1 year with recent acute exacerbation. Laboratory test demonstrated lactic acidosis. 18 F-FDG PET/CT was performed to exclude malignancy and showed generalized muscular hypermetabolism. Muscle biopsy combined with patient's history suggested mitochondrial myopathy. This report illustrates that mitochondrial myopathy may present as generalized muscular hypermetabolism on 18 F-FDG PET/CT and thus should be added to the differential diagnoses.